ID: 111: THE S1P TRANSPORTER, SPNS2, MEDIATES HGF-INDUCED LAMELLIPODIA FORMATION AND MIGRATION OF HUMAN LUNG ENDOTHELIAL CELLS. Issue 4 (22nd March 2016) - Fu, P; Usatyuk, PV; Ebenezer, DL; Natarajan, V
Abstract : Rationale: We have demonstrated earlier that HGF-induced lamellipodia formation in human lung microvascular endothelial cells (HLMVECs) was through c-Met receptor tyrosine kinase and PI3 kinase/Akt signal transduction. Here, we show that HGF-mediated lamellipodia formation is dependent on intracellular S1P generation mediated by sphingosine kinase 1 (SphK1), the S1P transporter, Spns2 and S1P1 in HLMVECs. Methods: HLMVECs were treated with HGF (20 ng/ml) for different time points. Lamellipodia were detected after HGF treatment by immunofluorescent staining of Spns2, cortactin and actin in lamellipodia, and lamellipodia were quantified by measuring cell periphery fluorescence intensity. Pearson's correlation coefficient was used to statistically quantify co-localization of proteins in lamellipodia. Endogenous SphK activity was blocked by SphK1 specific inhibitor PF-543, and expression of SphK1 in cells was down-regulated by siRNA. Cellular S1P levels were quantified by mass spectrometry. Results: HGF stimulated phosphorylation of SphK1, and its localization to lamellipodia of HLMVECs. Down-regulation of SphK1, but not SphK2, with siRNA or inhibition of SphK1 with PF-543 (1–5 µM) attenuated HGF-induced lamellipodia formation in HLMVECs. The HGF-mediated phosphorylation of SphK1 and its localization in lamellipodia was dependent on PI3K/Akt and ERK1/2 signaling apthways. HGF increased S1P levels in HLMVECs, which was blocked by inhibition of SphK1 with PF-543. Further, HGF induced serine phosphorylation and translocation of Spns2, the S1P transporter, to lamellipodia, which was Akt dependent. The HGF-induced lamellipodia formation in HLMVECs was blocked by down-regulation of Spns2, suggesting extracellular action of S1P in lamellipodia formation. Down-regulation of S1P1, but not S1P2 or S1P3, with siRNA attenuated HGF-induced lamellipodia formation. Further, HGF stimulation enhanced association of Spns2 with S1P1 and blocking SphK1 activty with PF-543 attenuated the association between Spns2 and S1P1 . Additionally, HGF-induced migration of HLMVECs was attenuated by down-regulation of Spns2. Conclusion: These results suggest that HGF/c-Met mediated lamellipodia formation and motility is dependent on intracellular generation of S1P via activation and localization of SphK1 to cell periphery and Spns2 mediated transport of S1P to outside for signaling via S1P1 in HLMVECs. This work was supported by NIH/HLBI P01 HL98050 to VN.